2002
DOI: 10.1038/sj.ejhg.5200842
|View full text |Cite
|
Sign up to set email alerts
|

A genome scan for loci influencing anti-atherogenic serum bilirubin levels

Abstract: Epidemiological studies have shown an association of decreased serum bilirubin levels with coronary artery disease. Two segregation analyses in large pedigrees have suggested a major gene responsible for high bilirubin levels occurring in about 12% of the population. Based on a recessive model from a previous segregation analysis, we performed a genome scan using 587 markers genotyped in 862 individuals from 48 Utah pedigrees to detect loci linked to high bilirubin levels. As a complementary approach, non-para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 49 publications
5
30
1
1
Order By: Relevance
“…Previous studies suggest that the TA repeats might be the key polymorphism within the UGT1A1 gene controlling bilirubin levels in people free of kidney failure (16,17). In the study presented here, for the first time, we demonstrated that UGT1A1*28 polymorphism may modify serum bilirubin levels and associate with CV events and mortality among patients undergoing chronic HD.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Previous studies suggest that the TA repeats might be the key polymorphism within the UGT1A1 gene controlling bilirubin levels in people free of kidney failure (16,17). In the study presented here, for the first time, we demonstrated that UGT1A1*28 polymorphism may modify serum bilirubin levels and associate with CV events and mortality among patients undergoing chronic HD.…”
Section: Discussionmentioning
confidence: 51%
“…Recent independent genome-wide linkage scans have identified a major locus in the chromosomal 2q telomere controlling serum bilirubin concentrations (16,17). The identified chromosomal region harbors the uridine diphosphate-glucuronosyltransferase (UGT1A1) gene.…”
Section: Introductionmentioning
confidence: 99%
“…By linkage analysis we recently identified a region on chromosome 2q significantly linked to bilirubin concentration (17 ), a finding that was subsequently confirmed by investigators for the Framingham Heart Study (18 ). The identified chromosomal region harbors the gene for the uridine diphosphate glucuronosyltransferase (UGT1A1, 6 UDP glucuronosyltransferase 1 family, polypeptide A1), the major enzyme of bilirubin glucuronidation, which mainly determines bilirubin elimination in humans.…”
Section: © 2008 American Association For Clinical Chemistrymentioning
confidence: 70%
“…[11][12][13] Previous linkage studies identified a major locus at the chromosome 2q telomere that affects bilirubin concentrations. 14,15 These 2 studies revealed a logarithm of the odds score of 3.8 and 3.2, respectively, spanning a region of 22 centimorgans (logarithm of the odds-1 supporting interval). One obvious candidate gene under the linkage peak is the gene that encodes hepatic bilirubin uridine diphosphateglucuronosyltransferase (UGT1A1), which is the only enzyme that contributes substantially to bilirubin glucuronidation and thus enhances bilirubin elimination.…”
Section: Clinical Perspective P 1481mentioning
confidence: 99%